2009
DOI: 10.1523/jneurosci.5216-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Spinogenesis and Pruning Scales across Functional Hierarchies

Abstract: Spinogenesis and synaptic pruning during development are widely believed to subserve connectional specificity in the mature CNS via Hebbian-type reinforcement. Refinement of neuronal circuit through this "use it or lose it" principle is considered critical for brain development. Here we demonstrate that the magnitude of spinogenesis and pruning in the basal dendritic trees of pyramidal cells differ dramatically among sensory, association, and executive cortex. Moreover, somewhat counterintuitively, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
160
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(175 citation statements)
references
References 22 publications
(27 reference statements)
10
160
3
Order By: Relevance
“…In low-expanding visual and auditory cortex (Heschl's gyrus), synaptic density is 50-100% greater and is closer to peak density than the high-expanding middle frontal gyrus (1). The neonatal macaque visual and auditory cortex are close to mature dendritic spine and dendritic field area, whereas the anterior prefrontal and lateral temporal cortex have approximately half the density and field area found in adulthood (23)(24)(25). In newborn humans, the local cerebral metabolic rate for glucose is markedly higher (by 15-25%) in the low-expanding medial temporal and visual cortex than in the high-expanding dorsolateral prefrontal cortex (DLPFC) (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In low-expanding visual and auditory cortex (Heschl's gyrus), synaptic density is 50-100% greater and is closer to peak density than the high-expanding middle frontal gyrus (1). The neonatal macaque visual and auditory cortex are close to mature dendritic spine and dendritic field area, whereas the anterior prefrontal and lateral temporal cortex have approximately half the density and field area found in adulthood (23)(24)(25). In newborn humans, the local cerebral metabolic rate for glucose is markedly higher (by 15-25%) in the low-expanding medial temporal and visual cortex than in the high-expanding dorsolateral prefrontal cortex (DLPFC) (26).…”
Section: Discussionmentioning
confidence: 99%
“…Selected regions of interest were mapped to macaque surface atlas (Fig. 5) according to the following study references: V1, MT, Tea (58); V2, LIP, MT 7a (59); FEF (28); TEpd, PFC (23).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, it has been shown that pyramidal neurons of the prefrontal cortex are characterized by more elaborate dendritic trees than other cortical areas, to support increased connectivity from integrating diverse corticocortical inputs and to orchestrate cognitively complex behaviors (20,31,32,40). Although dendritic arbors are more extensive in the prefrontal cortex relative to other cortical regions in adult humans (31), chimpanzees (32), and macaques (20), the timing of development of these neuronal specializations appears to be species-specific (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas synaptogenesis occurs synchronously across the entire cerebral cortex in macaques (9), it appears delayed in the prefrontal region in humans (11). In macaques, moreover, densities of spines located on the dendrites of prefrontal pyramidal neurons are higher than other areas from the time of birth and throughout postnatal development (13). In humans, however, dendritic arbors of prefrontal cortex pyramidal neurons reach adult-like morphological complexity and spine density later in development than dendritic arbors in sensory and motor cortices (14).…”
mentioning
confidence: 99%
“…After the initial development in the mammalian brain, synapse elimination and refinement occur though interaction with the environment via sensory inputs (Huttenlocher et al, 1982;Elston et al, 2009). However, the detailed mechanisms of this elimination and refinement remain unclear.…”
Section: Relationship Between Synaptic Densities and Network Electricmentioning
confidence: 99%